2012
DOI: 10.5923/j.ijaf.20120203.05
|View full text |Cite
|
Sign up to set email alerts
|

Substitutes or Complements?: Formal and Informal Credit Demand by Maize Farmers in Ashanti and Brong Ahafo Regions of Ghana

Abstract: This study examines credit demand by maize farmers and analyses factors influencing their use of informal and formal credits. The analysis is based on data collected from a survey of 590 maize farmers in seven districts of Ashanti and Brong Ahafo Regions of Ghana during May-July 2010. Descriptive statistics, probit and bivariate probit models were used to analyse the data. The study revealed informal credit sources for maize farmers as relatives and friends, traders and private money lenders. Maize traders are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 4 publications
2
7
0
1
Order By: Relevance
“…The male respondents are 25% more probable to take part in the credit programme compared with female. The result supports the finding of Awunyo-Vitor and Abankwah (2012) which revealed that the probability of male farmers participating in a credit programme is higher than that of female farmers. This is because male farmers tend to own larger farm sizes with associated higher demand for finance than their female counterparts.…”
Section: Factors Influencing Farmers' Participation In the Hunger Project Credit Programmesupporting
confidence: 89%
“…The male respondents are 25% more probable to take part in the credit programme compared with female. The result supports the finding of Awunyo-Vitor and Abankwah (2012) which revealed that the probability of male farmers participating in a credit programme is higher than that of female farmers. This is because male farmers tend to own larger farm sizes with associated higher demand for finance than their female counterparts.…”
Section: Factors Influencing Farmers' Participation In the Hunger Project Credit Programmesupporting
confidence: 89%
“…Vuong Quoc (2012) further illustrates the significance of belonging to the Vietnamese ethnicity and the educational level when it comes to loan accessibility in Vietnam. Awunyo-Vitor and Abankwah (2012) show that there is a positive and statistically significant relationship between a farmer's years of education and their demand for formal credit. They argue that this might be due to the farmers' increased ability to understand procedures and policies of MFIs.…”
Section: Methodsmentioning
confidence: 94%
“…With respects to gender distribution, males form 63.3% while female respondents form 33.7% of the respondents. Gage and Njogu [23] commented that in agricultural communities in Ghana, men were usually responsible for Age of respondent at the time of interview in years X 2 Gender of respondent specified as a dummy variable (0=male, 1=female) X 3 Years of education measured in years X 4 Household size of the respondent X 5 Respondent's ethnicity specified as categorical variable (0= Ga, 1= Ewe, 2=Akan, 3 Northerner) X 6 Experience in tomato production measured in years X 7…”
Section: Demographic and Socio-economicmentioning
confidence: 99%
“…Since consumption is spread all over the country, the commodity has to be transported over varied distances to consumers. The defective methods of picking, packing and transportation result in a large proportion of the commodity deteriorating in transit [5]. The extent of spoilage is stated as ranging between 5 and 50 per cent [6].…”
Section: Introductionmentioning
confidence: 99%